Loss Accounting And Local Wisdom: An Islamic Ethnomethodology Study - Thalib, Mohamad Anwar (Kodifikasia, 2025)
This study examines the practice of loss accounting carried out by fishermen in Gorontalo, based on local wisdom values, as a response to the dominance of Western accounting concepts that tend to overlook indigenous community-based approaches. The main objective of this research is to uncover the strategies used by fishermen to face and manage losses within their cultural and religious context. An Islamic ethnomethodological approach was employed in data analysis, which was conducted through five analytical stages: charity, knowledge, faith, revelation information, and courtesy. The results reveal two main strategies for minimizing loss: a fuel deposit system and side activities that generate additional income. These strategies are grounded in the values of sabari (patience) and sukuru (gratitude), derived from the Gorontaloan Islamic philosophy lumadu diila o’onto, bo wolu-woluwo, which means seeking both visible and invisible blessings. The fishermen’s loss accounting practices demonstrate a strong interconnection between spirituality, local culture, and economic management, offering a contextual alternative to conventional accounting systems. These findings provide important contributions for academics, policymakers, and practitioners in designing accounting frameworks that respect cultural and spiritual dimensions.